Experience of nutritional counselling in a nutritional programme in HIV care in the Tigray region of Ethiopia using the socio-ecological model - Fisaha Haile Tesfay; Anna Ziersch; Lillian Mwanri; Sara Javanparast (BMC, 2021)
Abstract Background In many resource-poor settings, nutritional counselling is one of the key components of nutrition support programmes aiming to improve nutritional and health outcomes amongst people living with HIV. Counselling methods, contents and recommendations that are culturally appropriate, locally tailored and economically affordable are essential to ensure desired health and nutritional outcomes are achieved. However, there is little evidence showing the effectiveness of counselling in nutritional programmes in HIV care, and the extent to which counselling policies and guidelines are translated into practice and utilised by people with HIV suffering from undernutrition. This study aimed to explore these gaps in the Tigray region of Ethiopia. Methods and participants A qualitative study was conducted in Tigray region Ethiopia between May and August 2016. Forty-eight individual interviews were conducted with 20 undernourished adults living with HIV and 15 caregivers of children living with HIV enrolled in a nutritional programme in three hospitals, as well as 11 health providers, and 2 programme managers. Data analysis was undertaken using the Framework approach and guided by the socio-ecological model. Qualitative data analysis software (QSR NVivo 11) was used to assist data analysis. The study findings are presented using the consolidated criteria for the reporting of qualitative research (COREQ). Result The study highlighted that nutritional counselling as a key element of the nutritional programme in HIV care varied in scope, content, and length. Whilst the findings clearly demonstrated the acceptability of the nutritional counselling for participants, a range of challenges hindered the application of counselling recommendations in participants' everyday lives. Identified challenges included the lack of comprehensiveness of the counselling in terms of providing advice about the nutritional support and dietary practice, participants' poor understanding of multiple issues related to nutrition counselling and the nutrition programme, lack of consistency in the content, duration and mode of delivery of nutritional counselling, inadequate refresher training for providers and the absence of socioeconomic considerations in nutritional programme planning and implementation. Evidence from this study suggests that counselling in nutritional programmes in HIV care was not adequately structured and lacked a holistic and comprehensive approach. Conclusion Nutritional counselling provided to people living with HIV lacks comprehensiveness, consistency and varies in scope, content and duration. To achieve programme goal of improved nutritional status, counselling guidelines and practices should be structured in a way that takes a holistic view of patient's life and considers cultural and socioeconomic situations. Additionally, capacity development of nutritional counsellors and health providers is highly recommended to ensure counselling provides assistance to improve the nutritional well-being of people living with HIV.